Pengelolaan Lingkungan Berbasis Pesantren (Studi Kasus di Pondok Pesantren Nurul Hakim Lombok) - Rihlah Nur Aulia; Dian Elvira Nanda Isnaini; Umi Khumairoh (Universitas Negeri Jakarta, 2017)
This study aims to find out the management of the pesantren-based environment in Pondok Pesantren Nurul Hakim, Lombok. The method used is qualitative research by collecting data through field observation, documentation, literature study and interview. This research concludes: first, Nurul Hakim Ponpes included in an ecopesantren category. Second, the aspect of ecopesantren done by pesantren Nurul Hakim lies in some aspects; the aspect of the boarding school policy, the hidden environmental curriculum, the participatory environmental activities and the existence of facilities and infrastructures that support the realization of environmental management.